Model laboratorium Kincir Air Untuk Irigasi Pertanian - Putra, Riyon Andeska; Rinaldi, Rinaldi; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Waterwheel comprises of giant wheel equipped with bamboo buckets which rotates due to water flow to lift water from the river to the higher elevation paddy field. The waterwheel model usedin this research was the undershoot water waterwheel. The waterwheel has 55 cm of diameter, 18 blades (6 cm-long and 6 cm-wide), and 1764 kg of weight. This research was done by varying the number and dimension of the boxes to obtain the waterwheel’s optimal number of boxes. The number of boxes variation was 6, 12, 18, 24, 30, and 36 boxes. The box quantity variation was 6.67 ml, 10.5 ml, and 16 ml. The water flow rate was not varied. The result of this research shows that the rotation rate of the waterwheel was affected by the velocity of water driving theblades. The number and volume of the boxes affect the rotation rate of the waterwheel. The maximum flow rate that could be lifted by the boxes was 474.44 ml/minute, 647.78 ml/minute,and 1083.33 ml/minute for type 1, 2, and 3 boxes, respectively.Keywords: model, waterwheel, undershoot